THE INFLUENCE OF BENSON RELAXATION TOWARDS THE LEVEL OF ANXIETY IN CERVICAL CANCER PATIENTS IN INPATIENT WARD OF CAMAR III AT GENERAL HOSPITAL OF ARIFIN ACHMAD PEKANBARU 2015 - YENNY SAFITRI (Jurnal Ners, 2017)
One of the therapy that can reduce anxiety is Benson relaxation. This therapy will inhibit the activity of the sympathetic nervous which will reduce oxygen consumption by the body and then the muscles are relaxed, causing a feeling of calm and comfortable. This study uses a quasi-experimental research design, with the approach of pretest-posttest design with control group, involving the control group in addition to the experimental group. With the use of accidental sampling technique then set 30 as sample. The measurement of anxiety exerts performed before and after treatment using Ratting Hamilton Anxiety Scale (HARS) the intervention is given for 1 week. The results of statistical tests using independent t test obtained p-value = 0.000 significant p-value <0.05 then Ho is rejected, which means that the influence of Benson relaxation on the level of anxiety in patients with cervical cancer before and after Benson relaxation therapy.